MORPHO METRICAL ASSESSMENT OF PANCREAS SHOWING PATERNAL DIABETES HERITABLE TO FIRST GENERATION MALE LITTERS AND THERAPEUTIC IMPACT OF BLACK PLUM (Syzigium cumuni) - REKHA, KUMARI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Present study focused on morpho metrical assessment of Pancreatic parameter (pancreatic mass and pancreatic diameter) of first generation male litters obtained from diabetic male mated with normal female and therapeutic impact of black plum. Alloxan persuade diabetic male mice leads to decrease in sufficient insulin dissimulation in them. Fixed dose of Black plum (Syzigium cumuni) seed powder were fed along with food to First generation and morphometry of pancreas was done. Black plum (Syzigium cumuni) seed powder reinstate the histoarchitecture of pancreatic β cells and accelerate the secretion of pancreatic insulin in First generation male mice. Blood glucose levels were observed to recur to their normal levels. Significant reduction in the alterations or abnormalities (i.e. smaller and more irregular shaped islets) in First generation male mice were noticed. Hyperglycemia may affect the epigenetic modifications during spermatogenesis and these epigenetic alterations in pancreatic structures cannot be normalized by giving normal diet implying that these alterations were transgenerational and may inherited through male germ line and move onto more than one generations. In near future, transgenerational or epigenetic factors may be regarded as huge aspect in assessing risk of diabetes.